"Rest before Labour": The Pre-Text/s of Blake's The Four Zoas - Lussier, Mark (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractThis essay explores the ambiguities and ironies resident in the aphoristic phrase "Rest before Labour," which William Blake positions as the portal of "readerly" entry into his preliminary epic Vala, or The Four Zoas, which Blake never published. The "Rest" implied (the slumber of Albion, read historically and psychologically) occurs in the remainder of the poem yet functions as the boundary condition for the work itself—the first pre-text for this problematic work one might say. The "Labour" implied (the nightmare of alienation and fragmentation that ensues within Albion's sleep) occurs in the space-time of dreams across nine nights yet functions as the state of mind-matter relations in the waking world—the second pre-text for the work. The labor implicated in this dream narrative (visionary transformation of the public sphere) can only be achieved upon completion of the poem, again rendering all labors within the poem as pre-text for historical action. Once the work concludes its inner and outer operations (its labors, so to speak), reception dynamics shift the discursive arena to its readers, enacting a psycholinguistic transference until, ideally, Albion's awakening becomes our own. The poem's dream-work, then, inverts traditional associations of "rest" and "labour," and the implications of such an inversion best emerge when comparing Blake's view of dream-work with the critical elements articulated by Julia Kristeva in her analysis of a revolution in poetic language following the Romantic period itself. Kristeva's insightful analysis helps map Blakean cartographies of inner and outer symmetry.